NURCHOLISH MADJID INCLUSIVE THINKING IN RELIGION AND STATE RELATIONS IN INDONESIA - Sumanta Sumanta (JURNAL YAQZHAN: Analisis Filsafat, Agama dan Kemanusiaan, 2022)
The subject of the relationship between religion and the state in society appears to be inexhaustible in modern Islamic studies discourse. The legal-formalistic understanding of Islam, which requires Islam to be manifested in the form of legalism and symbolism in the form of an Islamic state, has become something that appears to be discussed in various parts of the world, including Indonesia, especially since the Prophet Muhammad's death. In this context, it's worth considering the views of one of Indonesia's Islamic leaders, Nurcholis Madjid, on inclusivity in studying the relationship between religion and the state, where he proposes a democratic approach. In the elements of his thinking and speech, this research paper will further analyze the relationship between religion and the state.